2021
DOI: 10.1111/iere.12499
|View full text |Cite
|
Sign up to set email alerts
|

Components of Uncertainty

Abstract: Uncertainty is acknowledged to be a source of economic fluctuations. But, does the type of uncertainty matter for the economy's response to an uncertainty shock? This article offers a novel identification strategy to disentangle different types of uncertainty. It uses machine learning techniques to classify different types of news instead of specifying a set of keywords. The article finds that, depending on its source, the effects of uncertainty on a macroeconomic variable may differ. I find that both good (ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…It is one of the most popular topic algorithms in the NLP literature and used here because of its simplicity, because it has proven to classify text in much the same manner as humans would do (Chang et al (2009)), and because it delivers interpretable output. For these reasons it has also been one of the most widely used NLP algorithms in recent economic applications (Hansen and McMahon (2016), Larsen (2017), Larsen and Thorsrud (2017), Hansen et al (2018), and Dybowski and Adämmer (2018)).…”
Section: News Data and Topicsmentioning
confidence: 99%
“…It is one of the most popular topic algorithms in the NLP literature and used here because of its simplicity, because it has proven to classify text in much the same manner as humans would do (Chang et al (2009)), and because it delivers interpretable output. For these reasons it has also been one of the most widely used NLP algorithms in recent economic applications (Hansen and McMahon (2016), Larsen (2017), Larsen and Thorsrud (2017), Hansen et al (2018), and Dybowski and Adämmer (2018)).…”
Section: News Data and Topicsmentioning
confidence: 99%
“…While actively studied by economics and business scholars, uncertainty shocks have received barely any attention from international relations researchers. In relation to firms, studies showed that organizations often adopt a ‘wait and see’ strategy in response to uncertainty shocks (Bloom, 2009), by pausing investment and hiring (Bloom, 2009; Larsen, 2021). In other words, unlike common situations of crisis with high levels of certainty (e.g.…”
Section: Exogenous Events As Sources Of Organizational Changementioning
confidence: 99%
“…Similarly to our findings, he also documents a negative response of real activity to a financial uncertainty shock. Interestingly, Larsen (2021) shows that not all types of uncertainty are alike. For instance, uncertainty surrounding future mergers and acquisitions is found to be positively correlated with the Norwegian business cycle.…”
Section: Related Literaturementioning
confidence: 99%